Reclassification of Nocardia species based on whole genome sequence and associated phenotypic data. (July 2018) - Tamura, Tomohiko; Ohji, Shoko; Ichikawa, Natsuko; Hosoyama, Akira; Yamazoe, Atsushi; Hamada, Moriyuki; Komaki, Hisayuki; Shibata, Chiyo; Matsuzawa, Tetsuhiro; Gonoi, Tohru; Suzuki, Ken-ichiro; Fujita, Nobuyuki
Abstract Type strains of 72 validatedNocardia species were phylogenetically analyzed based on the multilocus sequence analysis (MLSA) concatenatedatpD–groL1–groL2–recA–rpoA–secY–sodA–ychF . Furthermore, their similarity based on digital DNA–DNA hybridization (dDDH) was calculated.Nocardia soli, Nocardia cummidelens andNocardia salmonicida, Nocardia nova andNocardia elegans, Nocardia exalbida andNocardia gamkensis, andNocardia coubleae andNocardia ignorata formed coherent clades, respectively. Moreover, each set showed over 70% relatedness by dDDH and shared common phenotypic characteristics. Therefore, we propose a reclassification ofNocardia soli and Nocardia cummidelens as a later heterotypic synonym ofNocardia salmonicida, Nocardia elegans as a later heterotypic synonym ofNocardia nova, Nocardia gamkensis as a later heterotypic synonym ofNocardia exalbida, andNocardia coubleae as a later heterotypic synonym ofNocardia ignorata .